Trainer Effectiveness in Basic Electrical and Electronic Practices in Vocational High Schools - Sukardjo, Moch; Uswatun Khasanah; Fatur Rahman (JTP - Jurnal Teknologi Pendidikan, 2022)
Basic Electricity and Electronics is one of the subjects in VHS. This subject teaches theory and practice. Practical subject matter includes: how to measure the components of resistors, capacitors, coils, transistors and other components. This study aims to determine the effectiveness of practical trainers that have been developed for basic electricity and electronics subjects that have been developed and designed as practical learning media. The method used in this study is research and development (R n D), using the Hannafin and Peck model. The feasibility of practice trainers is based on the results of expert assessments, namely (1) assessment by material experts with a percentage gain of 92.50%, (2) assessment by media experts with an acquisition percentage of 82.60%, (3) assessment of student use obtains a percentage of 86.89 %. from the results of the assessment of the experts and students, it can be concluded that the basic electronics practice trainer is said to meet the requirements and is suitable for use as a learning medium for Basic Electricity and Electronics Class X for the Department of Audio-Video Engineering at Vocational High Schools. For the effectiveness of the trainers that have been developed it is done by comparing the results of the initial test with the results which result in an increase in learning outcomes by an average of 42.98%, so it is concluded that there is an increase in learning outcomes. To test the effectiveness obtained tcount = 98.2 and ttable = 2.056, because tcount> ttable, it can be said that this trainer is effective for use in practice. A gain value of 0.8 is in the range > 0.7, this means an increase in basic electrical and electronics practical skills before and after using a basic electrical and electronics practicum trainer with a high category.